Investigation of dependencies of resonance circuit characteristics on design and electric value of "inductor - heated object" system; Bulletin of the Tomsk Polytechnic University; Vol. 310, № 1 - Zeman S. К. (Power engineering, 2007)
Заглавие с титульного листа